The Significance of 'Critical Border Thinking' and 'Languaging' in the Sri Lankan Context - Tantrigoda, Pavithra; de Silva, Esther Surenthiraraj (University of Colombo, 2010)
This paper will examine the notion of "critical border thinking" and its significance for postcolonial societies such as Sri Lanka. Further, it will explore the role of 'languaging' in relation to "critical border thinking", paying attention to the Sri Lankan context. Borders are commonly regarded as spatial or geographic boundaries that indicate territorial, geopolitical divisions. Borders can also signify "subjective (e.g. cultural) and epistemic" divisions and, "contrary to frontiers, the very concept of 'border' implies the existence of people, languages, religions and knowledge on both sides." Despite the arbitrary, contested and constructed nature of borders, these are made to signal an important difference between the 'insiders'/'outsiders' and 'us'/'them'. In terms of epistemology, such borders function to validate certain forms of knowledge, while invalidating and delegitimizing others. Santos (2007) claims that 'abyssal cartography' that consists of a system of visible (this side of the line) and invisible (other side of the line) distinctions premised on colonial difference is constitutive of modern knowledge (p.6). While for the Western nations, imperialism led to a rearticulation of epistemic frontiers, for many colonized nations, it registered a moment of 'epistemic violence' and/or devaluation of native knowledges. Hence, critical border thinking (or border epistemology) is a politico-epistemological project that undertakes to re-write "geographic frontiers, imperial/colonial subjectivities and territorial epistemologies" from the borders and, thus, it is a 'de-colonial project'. It "emerged from and as a response to the violence (frontiers) of imperial/territorial epistemology and the rhetoric of modernity (globalization) of salvation that continues to be implemented on the assumption of the inferiority or devilish intentions of the Other and, therefore, continues to justify oppression and exploitation, as well as eradication of the difference" (Mignolo & Tlostanova, 2006, p. 206). While examining the significance of the above concept, this paper will argue that far from being a unitary space, the space of border thinking itself is highly fraught with dissidence, tensions and ambivalences. This is specially so with the emeregence of nation states and politics of ethnonationalism. For, epistemology came to be entwined with national ideologies that presuppose the purity of race, as well as language. Language occupies a pivotal place in the concept of border epistemology. Epistemology is interwoven into language and it constructs and shapes our understanding of the world. Also, it is closely linked with communal and geopolitical formations (Mignolo and Tlostanova, 2006, p. 207). While prestige is accorded to languages such as English and French and the knowledge produced therein, the 'Oriental' languages (i.e. Sanskrit) and epistemology were/are denied such recognition. The emphasis placed on national languages in the decolonizing process has intitiated a different set of politico-ideological issues. Importantly, 'critical border thinking' involves 'languaging' and 'bilanguaging' and it "opens up to a postnational imaginary" (Mignolo, 2000, p. 253). This paper will highlight the significance of languaging and bilanguaging in the Sri Lankan context in relation to the concept of 'border thinking'.